Inter-Caste Marriage and the Illusion of a Casteless Society: A Critical Study of Kanyadan (Sudurpaschim Spectrum, 2024)
Kanyadan critiques contemporary social reality, which is prevalent as the burning concepts of the upliftment of Dalits and the creation of a casteless society through inter-caste marriage. It endeavors to reveal the hollowness of the idealist view of envisioning a caste-free society through inter-caste marriage and inter-caste dining. This study aims to demonstrate the complications caused by inter-caste marriage, exposing it as a means to take revenge against the high caste, a reminder of past humiliation and psychological torments, and highlighting the ongoing debates between idealism and realism. Kanyadan was selected purposefully for data collection and approached with qualitative textual analysis. Data on revenge from Dalits, psychological misconduct, and support for idealistic and realistic concepts were selected and coded, determining the categories to develop the broad theme of social commentaries concerning inter-caste marriage. Themes were analyzed, making connections among the categories and approaching with the theories of caste, hegemony, resistance, and subaltern, situating the primary data against the historical timeline to derive the resemblance of primary data with contemporary society, providing the commentaries on the then society, particularly the issues and concept on caste. This study demonstrates that the idealist view of a caste-free society does not contribute to the upliftment of Dalits but instead helps in revenge against the high class and reminds the past humiliation to Dalits.